2017
DOI: 10.1111/adb.12506
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine‐induced molecular alterations are modulated by GABAB receptor activity

Abstract: It has been demonstrated that GABA B receptors modulate nicotine (NIC) reward effect; nevertheless, the mechanism implicated is not well known. In this regard, we evaluated the involvement of GABA B receptors on the behavioral, neurochemical, biochemical and molecular alterations associated with the rewarding effects induced by NIC in mice, from a pharmacological and genetic approach. NIC-induced rewarding properties (0.5 mg/kg, subcutaneously, sc) were evaluated by conditioned place preference (CPP) paradigm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The stimulation of GABA B -R by baclofen is linked to a reduction in addiction-related behavior towards substances such as nicotine, cocaine and alcohol in animal models [79,84]. Drugs of abuse stimulate the mesolimbic system in the brain that controls the release of the reward-associated neurotransmitter dopamine [85]. A recent study showed that the rewarding effect of nicotine was reduced in animals pre-treated with baclofen [85].…”
Section: Gaba B Receptor Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of GABA B -R by baclofen is linked to a reduction in addiction-related behavior towards substances such as nicotine, cocaine and alcohol in animal models [79,84]. Drugs of abuse stimulate the mesolimbic system in the brain that controls the release of the reward-associated neurotransmitter dopamine [85]. A recent study showed that the rewarding effect of nicotine was reduced in animals pre-treated with baclofen [85].…”
Section: Gaba B Receptor Pathophysiologymentioning
confidence: 99%
“…Drugs of abuse stimulate the mesolimbic system in the brain that controls the release of the reward-associated neurotransmitter dopamine [85]. A recent study showed that the rewarding effect of nicotine was reduced in animals pre-treated with baclofen [85]. Nicotine stimulates the nicotine acetylcholine receptors (nAchRs) located on GABAergic, glutamatergic and dopaminergic neurons, which causes release of dopamine.…”
Section: Gaba B Receptor Pathophysiologymentioning
confidence: 99%
“…The GABA B -R is linked to a variety of neurological and neuropsychiatric disorders including memory and learning deficits, addiction, epilepsy, anxiety and depression, and is an interesting target for drug intervention [15,16,17,18]. However, at present, the agonist baclofen (β-(4-chloro-phenyl)GABA) is the only marketed drug targeting the GABA B -R. Baclofen is used as a muscle relaxant and antispastic agent to treat muscle spasticity and other muscle symptoms caused by e.g., multiple sclerosis [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Such a speculative mechanism would have to be activity independent, though, since our experiments with nicotine were performed in the continued presence of TTX. Prolonged exposure of VTA slices to nicotine could induce glutamate, GABA, and/or endocannabinoid release that could then act on mGluR, GABA B , or CB1 G-protein-coupled receptors to attenuate optical activation of VGluT2 + or Gad2 + fibers (Merrill et al, 2015; Han et al, 2017; Varani et al, 2018). It is very unlikely, however, that nicotine suppresses release by interfering with a stimulatory action of endogenous ACh.…”
Section: Discussionmentioning
confidence: 99%